Sustainable Energy Management Design for Bario Microgrid in Sarawak, Malaysia - Adila, Fakhar; Ahmed Mohamed, Ahmed Haidar; Musse, Mohamud Ahmed; Rahman, A. K. (2018)
The use of diesel generators as a backup to supply the load demand in Bario is costly and environmentally troublesome. On the other hand, utilizing natural resources that form islanded microgrids located in different areas can pose peculiar energy management issues, particularly, when different energy providers manage the renewable and nonrenewable small powerhouses. This paper proposes a framework focusing on the design of sustainable aggregate management system for minimizing the operating time of diesel generators, and thus, reducing the fuel cost and increasing the battery lifetime, while at the same time protecting the environment. Initially, the paper discusses the structure of the existing system. Further, an energy management approach is presented for maximizing the generated power from the available renewable resources at different hours. The presented results show that the proposed sustainable design can be an effective method for planning the development of electrification in the rural areas of Sarawak.